Difficult Europeans: NATO and Tactical/Non-strategic Nuclear Weapons in the Cold War - Kris Stoddart (Diplomacy & Statecraft, 2017)
This analysis examines NATO’s tactical/non-strategic nuclear weapons in the Cold War both for their perceived deterrent value against the Soviet Union and Warsaw Pact and as potential war fighting weapons. Within this debate lay questions related to extended deterrence, security guarantees, regional or theatre conflict, and escalatory potential. A central tenet that emerged in Europe was that nuclear weapons needed emplacement on the territory of non-nuclear NATO members to make deterrence more tangible. It raised huge questions of consultation. Once the Soviet Union had intercontinental missiles, the credibility of American readiness to use nuclear weapons in defence of its allies came into question. European alternatives and different consultation mechanisms to facilitate nuclear use became central to intra-NATO relations. Actively debated across NATO, they directly concerned above all the United States, Britain, and France—the nuclear weapons states in the NATO area—and West Germany, the potential main battleground in a Warsaw Pact invasion. Although dormant in NATO since the end of the Cold War, these issues will likely see revisiting in both Europe and other regional trouble spots.